2011
DOI: 10.1111/j.1447-0756.2010.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spinal epidural hematoma at the 16th week of a twin pregnancy

Abstract: Spontaneous spinal epidural hematoma without discernable underlying conditions is a rare complication during pregnancy. We report a pregnant woman who developed the hematoma at 16 weeks of pregnancy; the earliest occurrence ever reported. A 36-year-old Japanese primipara with twins felt shoulder, neck and back pain at 16(+1) weeks with progressive quadriplegia. Magnetic resonance imaging revealed a mass in the C3-7 epidural space, compatible with a spinal epidural hematoma, and decompression was performed 9 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A further three articles were excluded; the first as it was the same case as reported in another study, published in another language, 9,10 the second because the article presented SEH occurring after chiropractic manipulation 11 and the third reported a case of unilateral epidural nerve root hematoma in a pregnant patient. 12 The remaining 21 articles were all case report design; 4,5,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] to be noted, the article by Tada et al 30 reported 3 cases, making a total of 23 cases (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further three articles were excluded; the first as it was the same case as reported in another study, published in another language, 9,10 the second because the article presented SEH occurring after chiropractic manipulation 11 and the third reported a case of unilateral epidural nerve root hematoma in a pregnant patient. 12 The remaining 21 articles were all case report design; 4,5,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] to be noted, the article by Tada et al 30 reported 3 cases, making a total of 23 cases (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…18 One patient presented with twin pregnancy. 28 The remaining 21 patients had no significant medical history.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many situations could contribute to this haematoma such as aretrial hypertension, vasculitis, ankylosing spondylitis, physical strain, coagulation disorders [1], angiolipoma [5], preeclampsia and hellp syndrome [6,7] and the use of low molecular weight heparin [8]. It occurs early in pregnancy [9], during second and third trimester and in the post partum stage as well [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported a woman with twin pregnancy suffering SSEH at the 16 th week of gestation 2 . To our knowledge, 14 cases of SSEH during pregnancy have been reported 2,3 : decompression surgeries were performed in all cases. Both veins and arteries can be candidates of origin for SSEH.…”
mentioning
confidence: 99%